(untitled) (INNOVATIVE ECONOMY, 2019)
Vatamaniuk-Zelinska U.Z., Nazar N.V., Kravtsova O.V. THE ROLE OF STRATEGIC PLANNING OF THE STATE BUDGET EXPENDITURES IN SUPPORT OF SOCIAL AND ECONOMIC DEVELOPMENT OF UKRAINE Purpose. The aim of the study is to determine the measures for balancing the income and expenditure part of the state budget of Ukraine based on the analysis of the planned indicators of their financial support for the period 2016-2018. Methodology of research. The results of the study are based on the use of abstract and logical analysis to determine the essence of strategic budget planning; statistical analysis – to establish the priorities of financing the expenditures of the State Budget of Ukraine; system and structural approach – to determine the accuracy of forecasts of social and economic development of the state and the amount of financial support of the primary expenditures. Key provisions, principles and methods of modern economic theory and theories of regulation, finance and economics are also the theoretical and methodological basis of the research. Findings. The priorities of the distribution of state expenditures have been determined on the basis of the assessment of the practical principles of the strategic budget planning of the expenditures of the State Budget of Ukraine. The main reasons for not fulfilling the description of the expenditure part of the state budget are substantiated. Proposals on ways of improving the domestic system of strategic budget planning are put forward. Originality. The necessity of shifting the terms of formation of macroeconomic indicators of the state development for the 4th quarter of the current year and setting the rate of reduction of the state debt in relation to the level of GDP in accordance with the terms of medium and long-term budget planning implementation is substantiated. This, unlike the current approach of implementing the strategic budget planning of the expenditures of the State Budget of Ukraine, will enable us to provide a more accurate macroeconomic forecast of the indicators of social and economic development of our state and their coordination with the primary goals of the state budget policy. Practical value. Improving the methodological, regulatory and legal framework of strategic budget planning will become a prerequisite for calculating the budget allocations of the main spending units for the future and will ensure the successful implementation of the timed fiscal policy. Key words: state budget; expenditures; forecasting; budget planning; fiscal policy; program-target method.